2006
DOI: 10.1021/ja057450h
|View full text |Cite
|
Sign up to set email alerts
|

Random Coils, β-Sheet Ribbons, and α-Helical Fibers:  One Peptide Adopting Three Different Secondary Structures at Will

Abstract: To potentially cure neurodegenerative diseases, we need to understand on a molecular level what triggers the complex folding mechanisms and shifts the equilibrium from functional to pathological isoforms of proteins. The development of small peptide models that can serve as tools for such studies is of paramount importance. We describe the de novo design and characterization of an alpha-helical coiled coil based model peptide that contains structural elements of both alpha-helical folding and beta-sheet format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 10 publications
5
102
0
4
Order By: Relevance
“…This observation suggests that an external driving force will be needed in vivo. The α-helix to β-sheet (α-to-β) transition in other coiled coils has been shown to be enhanced by mechanical force (21,22), high temperature (23), pH change (24), and high protein concentration (25). A mechanical force-induced α-to-β transition has been observed in fibrin (22), collagen, and vimentin (26).…”
Section: α-Helix To β-Sheet Transition In a Coiled Coil Is Promoted Bmentioning
confidence: 97%
“…This observation suggests that an external driving force will be needed in vivo. The α-helix to β-sheet (α-to-β) transition in other coiled coils has been shown to be enhanced by mechanical force (21,22), high temperature (23), pH change (24), and high protein concentration (25). A mechanical force-induced α-to-β transition has been observed in fibrin (22), collagen, and vimentin (26).…”
Section: α-Helix To β-Sheet Transition In a Coiled Coil Is Promoted Bmentioning
confidence: 97%
“…Previous studies by our group have shown that incorporation of three b-sheet preferring valine residues at the b, c, and f positions of the heptad repeat sufficiently enhance the amyloid-formation propensity of a 26-residue coiled-coil peptide. [24,26] Thus, three valine residues were incorporated into the model peptides presented here to yield an inherent competition between a-helical coiled-coil folding and the b-sheet rich amyloid structure.…”
Section: Peptide Designmentioning
confidence: 99%
“…[11,19,20] We have explored the a-helical coiled coil folding motif, which is very common in nature and has been extensively studied in recent years, proving its application as a reliable model system. [9,11,19,20,41] Furthermore, the design principles of coiled coils are very well understood, [21] and folding is based on oligomerization, which is also the foundation of amyloid formation. Coiled coils consist of at least two a-helices wrapped around each other in a slight superhelical twist.…”
Section: Introductionmentioning
confidence: 99%